The Shuwa Arabs of Borno: Their Migration and Socio-Economic Roles to the Development of Kanem Borno Empire - Gazali, Dr. Kalli Alkali Yusuf (Research Parks Publishers, 2023)
The objective of this article is to trace the history of Shuwa Arabs of Borno, their movements and migrations into Kanem Borno Empire. The article used desk review to gather secondary data related to the topic under investigation. The disastrous draught, human challenges, natural and man-made environmental circumstances, which affected the Sahelian zone of Africa south of Sahara and beyond, occasioned large-scale and mass migrations of people and livestock into grassland environment ever since. Indeed, these waves of people human migrations and movement constituted a major feature of the pre-colonial history of Nigeria, brought many people from various locations, to various environments. The new comers also had to adjust and adapt themselves to their new environments. Thus, the Shuwa Arabs who were originally from the Arabian Peninsula came and settled in Kanem Borno Empire as far back as 14th Century. Today they are predominantly found in eastern and central Borno State.